The Rapid Carbapenemase Detection Method (rCDM) for Rapid and Accurate Detection of Carbapenemase-Producing Enterobacteriaceae and Pseudomonas aeruginosa - Jing, Xiaopeng; Min, Xiaochun; Zhang, Xing; Gong, Lin; Wu, Tingting; Sun, Ruiling; Chen, Liujun; Liu, Rong; Zeng, Ji (Frontiers in Cellular and Infection Microbiology, 2019)
This study aimed to design a new method for rapid and accurate detection of carbapenemase phenotypes based on the simplified carbapenem inactivation method (sCIM). We evaluated the sensitivity and specificity of the method, called the rapid carbapenemase detection method (rCDM), for the detection of carbapenemase-producing Enterobacteriaceae and Pseudomonas aeruginosa. A total of 257 Enterobacteriaceae, 236 P. aeruginosa, and 20 Acinetobacter baumannii isolates were tested. Phenotypic evaluations were performed using rCDM, sCIM and mCIM. For Enterobacteriaceae, the sensitivity of rCDM was 100% and the specificity was 99.6%. For P. aeruginosa, the sensitivity of rCDM was 97.4% and the specificity was 100%. Carbapenemase-producing A. baumannii were not detected by rCDM. The concordance rate of rCDM and sCIM for Enterobacteriaceae and P. aeruginosa was 99.8%, with the exception of one P. aeruginosa isolate that expressed the blaVIM-4 gene. The concordance rate of rCDM and mCIM for Enterobacteriaceae and P. aeruginosa was 100%. rCDM can be used to accurately detect carbapenemase-producing Enterobacteriaceae and P. aeruginosa in 56 hours and is suitable for routine use in most clinical microbiology laboratories.